2005
DOI: 10.1161/circulationaha.104.516278
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Human Myeloperoxidase by Macrophages Promotes Atherosclerosis in Mice

Abstract: Background-Myeloperoxidase (MPO) colocalizes with macrophages in the human artery wall, and its characteristic oxidation products have been detected in atherosclerotic lesions. Thus, oxidants produced by the enzyme might promote atherosclerosis. However, macrophages in mouse atherosclerotic tissue do not express MPO. Therefore, mice are an inappropriate model for testing the role of MPO in vascular disease. To overcome this problem, we generated and studied transgenic (Tg) mice that contained the human MPO gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
92
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 152 publications
(100 citation statements)
references
References 45 publications
7
92
0
1
Order By: Relevance
“…This promotor is absent in mice, a finding that may partially explain the marked absence of MPO or MPO activity in the mouse model and the failure of MPO-deficient mice to ameliorate atherosclerosis. Repopulating the bone marrow of LDLr -/-mice with bone marrow from transgenic mice expressing human myeloperoxidase resulted in increased atherosclerosis (57). Another study, utilizing the overexpression of different human MPO allele polymorphisms in the promoter region, likewise demonstrated increased aortic lesions in male mice only, thus highlighting the role of estrogen in ameliorating MPO expression (77).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This promotor is absent in mice, a finding that may partially explain the marked absence of MPO or MPO activity in the mouse model and the failure of MPO-deficient mice to ameliorate atherosclerosis. Repopulating the bone marrow of LDLr -/-mice with bone marrow from transgenic mice expressing human myeloperoxidase resulted in increased atherosclerosis (57). Another study, utilizing the overexpression of different human MPO allele polymorphisms in the promoter region, likewise demonstrated increased aortic lesions in male mice only, thus highlighting the role of estrogen in ameliorating MPO expression (77).…”
Section: Discussionmentioning
confidence: 99%
“…Despite strong evidence of MPO activity in human atherosclerotic lesions (28,38,55), mouse models of non-CKD atherosclerosis have undetectable MPO oxidation products in mouse atheroma (56). Paradoxically, MPO-deficient mice exhibit exaggerated atherosclerosis, although a study overexpressing MPO human transgene in macrophages showed increased atherosclerosis (57). This lack of MPO activity in mouse atheroma of non-CKD mice further highlights the need for an appropriate CKD-atherosclerosis model that demonstrates MPO activity in atheromatous lesions and lends itself to the systematic study of MPO action in CKD.…”
mentioning
confidence: 99%
“…Elevated levels of chlorotyrosine and nitrotyrosine, two characteristic products of MPO, have been detected in HDL from human atherosclerotic lesions (42,43,86,87). Moreover, when MPO is expressed in macrophages, atherosclerosis increases in LDL receptor-deficient mice (88), raising the possibility that the heme enzyme promotes atherosclerosis by targeting apoA-I for oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, only low levels of 3-chlorotyrosine, a characteristic product of myeloperoxidase, are detectable by mass spectrometry in mouse atherosclerotic tissue (22). Importantly, recent studies demonstrate that expression of human myeloperoxidase in macrophages promotes atherosclerosis in mice, providing direct evidence of the enzyme's causal role in atherogenesis (23).…”
mentioning
confidence: 99%